Nostalgia, guerra civil y franquismo en la narrativa española de finales del siglo XX. - Muñoz, Marianela (2012)
In this article one will attempt to analyze how with a nostalgic attitude the Spanish narrative of the 80's and 90's returns to the past: the Spanish Civil War years and the Franco era. There is a place for memory in this literature where the valuation of the facts has a double meaning. These texts dissolve the limits between personal and collective memory, upon reviewing and writing the period of the infant years, ("day dreams" for Freud or "gold age" for Bachelard) with its equivalence to the time of the Spanish War and Post War ("demythologization" for Navajas).